Experiences with Metal at the Belgian Ministry of the Interior - Deprez, F.; Adriaens, G.; Depoortere, B.; de Braekeleer, G. (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1994)
AbstractIn this paper we describe our experiences with Siemens Nixdorf's METAL system at the Belgian Ministry of the Interior. In the first part (sections 1,2,3 and 4) we report on the tuning phase during the pilot project. The second part (section 5) describes a prototypical real-life METAL translation session.